Recaudación del impuesto a la renta en la microempresa ecuatoriana - Carrillo Baldeón, Marcela Dolores (2024)
A systematic review was conducted on the production and publication of research papers on the study of Value Added Tax (VAT) Collection and Refund in Older Adults, during the period between 2012 and 2022 under the PRISMA approach (Preferred Reporting Items for Systematic reviews and Meta-Analyses). The objective of the analysis proposed in this document was to know the main characteristics of the publications registered in the Scopus and Wos databases and their scope in the study of the proposed variables, achieving the identification of 20 publications in total. Thanks to this first identification, it was possible to refine the results through the keywords entered in the search button of both platforms, which were TAX COLLECTION, SENIORS reaching a total of 10 documents, already excluding duplicates and those that did not meet the analysis criteria. From this analysis it is expected to know the contributions of the scientific community to the study of the management of taxes such as Value Added Tax (VAT) in the group of elderly people. It is expected to find a relationship between tax collection and refund policies and the management of the elderly by governmental entities.